Umur Memengaruhi Volume Semen dan Motilitas Spermatozoa Babi Landrace di Balai Inseminasi Buatan Baturiti, Tabanan, Bali (AGE AFFECTS SEMEN VOLUME AND MOTILITY OF SPERMATOZOA LANDRACE BOAR’S OF BATURITI ARTIFICIAL INSEMINATION CENTER, TABANAN, BALI) - Sumardani, Ni Luh Gde; Budaarsa, Komang; Putri, Tjok Istri; Puger, Antonius Wayan (Jurnal Veteriner, 2019)
Sperm quality have been associated with age for many years. This study aims to determine the inffluence of age to the volume and motility of Landrace boar’s sperm at Baturiti Artificial Insemination (AI) center. A Total of 300 ejaculates were used in this study. An ejaculate origin from five boar are a collection of five month. A complete randomized design (CRD) was used with two different boar of block ages, block A (2-4 year) and block B (6-8 year). Three or four glass slides were prepared for each boar sample; a drop of semen was placed on each glass slides. This sample was examined under the light microscope on five view field in each glass slides. The result of the research show that the Landrace boars in block A have semen volume average 273.60 mL and sperm motility 73.86%, while in block B the average semen volume was 107.66 mL and sperm motility 62.92%. It can be concluded that Landrace boars in block A had higher volume and sperm motility compared to Landrace boars in block B.